Microstructure, microhardness and wear behavior of TiN-based surface layers formed on commercially pure titanium Grades 2 and 4 by laser processing - Veselinov, Deyan; Koeva, Veneta; Yankova, Radostina; Rusev, Ivan; Rusev, Ivan; Skulev , Hristo (Archives of Metallurgy and Materials, 2026)
Microstructure, microhardness and wear behavior of TiN-based surface layers formed on commercially pure titanium Grades 2 and 4 by laser processing